Specific Effect of Trace Metals on Marine Heterotrophic Microbial Activity and Diversity: Key Role of Iron and Zinc and Hydrocarbon-Degrading Bacteria - Baltar, Federico; Gutiérrez-Rodríguez, Andrés; Meyer, Moana; Skudelny, Isadora; Sander, Sylvia; Thomson, Blair; Nodder, Scott; Middag, Rob; Morales, Sergio E. (Frontiers in Microbiology, 2018)
Marine microbes are an important control on the biogeochemical cycling of trace metals, but simultaneously, these metals can control the growth of microorganisms and the cycling of major nutrients like C and N. However, studies on the response/limitation of microorganisms to trace metals have traditionally focused on the response of autotrophic phytoplankton to Fe fertilization. Few reports are available on the response of heterotrophic prokaryotes to Fe, and even less to other biogeochemically-relevant metals. We performed the first study coupling dark incubations with next generation sequencing to specifically target the functional and phylogenetic response of heterotrophic prokaryotes to Fe enrichment. Furthermore, we also studied their response to Co, Mn, Ni, Zn, Cu (individually and mixed), using surface and deep samples from either coastal or open-ocean waters. Heterotrophic prokaryotic activity was stimulated by Fe in surface open–ocean, as well as in coastal, and deep open-ocean waters (where Zn also stimulated). The most susceptible populations to trace metals additions were uncultured bacteria (e.g.SAR324, SAR406, NS9, DEV007). Interestingly, hydrocarbon-degrading bacteria (e.g. Thalassolituus, Marinobacter, Oleibacter) benefited the most from metal addition across all waters (regions/depths) revealing a predominant role in the cycling of metals and organic matter in the ocean.